Paradiplomacy in Protecting West Kalimantan Migrant Workers in Malaysia during the Covid-19 Global Pandemic - Nugrahaningsih, Nurfitri; Nuzulian, Ully; Lutfie, Ratu Zahirah (Jurnal Hubungan Internasional, 2022)
The Covid-19 pandemic has required many countries to implement social restrictions and lockdown policies to prevent the spread of the virus within their borders. Malaysia was one of the countries that went into lockdown, which affected the temporary suspension of various non-essential socio-economic activities. As an implication, Malaysia had to implement a policy of massively repatriating some migrant workers to their countries of origin, including Indonesian migrant workers or Pekerja Migran Indonesia (PMI). The repatriation then became a challenge for the Indonesian Government, particularly in West Kalimantan, a province becoming the port of entry for PMI repatriation from Malaysia amidst the measures to prevent the spread of Covid-19. On the other hand, Malaysiaâ€™s measures are underway to protect PMI affected by Covid-19. The purpose of this study is to identify the factors causing the non-optimal paradiplomacy carried out by the West Kalimantan Provincial Government in dealing with the consequences of the Covid-19 outbreak on PMI. Protection of PMI in Malaysia should be a concern, considering the lockdown policies implemented in Malaysia require synergistic efforts by both governments and organizations holding a fundamental role in protecting the rights of PMI. This study employed an exploratory method and a qualitative approach with interview techniques as the primary source of data and literature review as a secondary source of data. The analysis in this study refers to the efforts of paradiplomacy proposed by Nugrahaningsih (2015), stating the necessity for mutual priority, wider participation, and government commitment. The results of this study revealed that the non-optimal paradiplomacy of the protection of migrant workers during the Covid-19 pandemic was caused by: (1) The absence of shared priority between both of West Kalimantan and Sarawak Governments regarding the protection of PMI, (2) The lack of participation from NGOs and civil society, and (3) The lack of commitment of the West Kalimantan Government to optimize the protection of PMI through the cooperation with the Sarawak Government (Malaysia).Â